Stochastic Iterative MIMO Detection System: Algorithm and Hardware Design - Jienan Chen; Jianhao Hu; Sobelman, Gerald E. (IEEE transactions on circuits and systems. I, Regular papers, 2015)
In this paper, we propose a Stochastic iterative multiple-input multiple-output (SIM) detection system based on the Markov chain Monte Carlo (MCMC) method. To improve the detection performance, the Gibbs sampler of the MCMC detector in the SIM is updated by the decoded bits from a channel decoder directly. The channel decoder is part of the updating unit that generates the new samples in the MCMC updating process. We also implement the SIM in a fully parallel scheme, which achieves a high detection speed. As a case study, we have designed and synthesized a 128-parallel 4 × 4 16-QAM SIM system using a CMOS 130 nm technology with a core area of 1.98 mm 2 and 457K logic gates. The SIM detection system can achieve a throughput of 787.5Mbps with a frame error rate (FER) 10 -3 at E b /N 0 =7dB, equaling the FER of a traditional iterative MIMO detection with four outer iterations.